The Roles of Educational Stakeholders in the Finnish Education System: Insights for Islamic Education in Indonesia - Nur Diyanto, Yuli; Eva Latipah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to identify the role of educational stakeholders in the Finnish education system and analyse the principles that can be used to improve the quality of Islamic education in Indonesia. Design/methods/approach – This research is library research that collects data from various sources, such as academic journals, books, websites, and also related publications. Content analysis is used to analyse data in three steps, namely data collection, data reduction, and drawing conclusions. Findings – The principles in the role of educational stakeholders in Finland could provide new insights to improve the quality of Islamic education in Indonesia. Some of these principles include intense collaboration between educational stakeholders, educational policies whose main aim is to support the student learning process, a participatory approach in making curriculum and educational policies, and a research-based approach is applied in the education system. Limitations – The data from this study is limited to the literature. Future research can use different approaches to get more in-depth results, for example by conducting in-depth interviews with educational stakeholders in Finland and Indonesia. Originality/value – This study provides a new perspective to improve the quality of Islamic Education in Indonesia from Finnish approach.